Amados aqueles que se sentam: imobilidade e hibridismo na trilogia do ser humano, de Roy Andersson - Lima, Natália Flávia Maia (2020)
The present work focuses on formal-discursive aspects of the Trilogy of the Human Being, by Swedish filmmaker Roy Andersson, composed of Songs of the Second Floor (2000), You, The Living (2007) and A Pigeon Sat On A Branch Reflecting On Existence (2014). Considering as the main focus the hybridism between cinema, painting and theater that the three films combine, we chose immobility (of bodies and the camera) as the most specific object of analysis, regarding it as the line that sews the three languages: from cinema to painting, due to the “pensive” engagement that the fixed image offers, associated with issues of temporality and pregnance; and from cinema to theater, through correlations with statism in the dramaturgy of Samuel Beckett. Keywords: Roy Andersson. Trilogy of the Human Being. Immobility. Language Hybridism